Pengaruh Celebrity Endorsement terhadap Keputusan Pembelian Produk Fashion di Butik Akzr.Id Kota Makassar - Ayyada Nadhifa; Abdi Akbar Idris; Muhammad Ichwan Musa (Trending: Jurnal Manajemen dan Ekonomi, 2024)
The purpose of this study was to determine the effect of Celebrity Endorsement on purchasing decisions for fashion products at Akzr.id boutique in Makassar City. The data used in this study were primary data as many as 100 samples. This type of research is included in quantitative research. The population in this study were consumers of the Akzr.id boutique in Makassar city. The methods used to analyze the relationship between the independent variable and the dependent variable are descriptive analysis, assumption test, validity test, reliability test, t test, Heteroscedasticity Test, and simple linear regression analysis. The results showed that Celebrity endorsement has a positive and significant effect on purchasing decisions on fashion products at Akzr.id boutique in Makassar City.